COLLABORATIVE LEARNING: STRENGTHENING LEARNER’S INTERPERSONAL SKILLS - Rukhiya Begum , Dr R Naga Dhana Lakshmi, G Vijaya Simha Goud (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Nowadays critical thinking, interpersonal skills, persuasive thinking, and emotional intelligence are more important skill for millennial students. These skills are required for the job force in the twenty-first century. This study is on the present teaching and learning experiences in engineering colleges in India. The recommended collaborative learning approach that can be applied in ESL (English as a second language) classroom in Telangana state, India. This paper discusses the planning, designing, and implementing collaborative activity and the challenges faced by the teachers while conducting the activity. A descriptive study was adopted in this research. The study was on second-year first-semester engineering students and the strength was sixty students, were divided into twelve groups and each group consisted of five students. In this study, Jigsaw activity was conducted as a sample to test the student’s improvement. The objective of the study is to improve these learners' social communication skills, critical thinking, and complex problem-solving skills by coordinating with others. This paper clarifies the concept of collaborative learning by presenting and analyzing the education benefits of collaborative techniques. The shift of teacher-centered to learner-centered promotes all the above-said skills.